2001
DOI: 10.2136/sssaj2001.1761
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Climate and Parent Material on Chemical Weathering in Loess‐derived Soils of the Mississippi River Valley

Abstract: Peoria Loess‐derived soils on uplands east of the Mississippi River valley were studied from Louisiana to Iowa, along a south‐to‐north gradient of decreasing precipitation and temperature. Major element analyses of deep loess in Mississippi and Illinois show that the composition of the parent material is similar in the northern and southern parts of the valley. We hypothesized that in the warmer, wetter parts of the transect, mineral weathering should be greater than in the cooler, drier parts of the transect.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
136
2
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(142 citation statements)
references
References 38 publications
3
136
2
1
Order By: Relevance
“…The model was also consistent with a small amount of dolomite at depth in pedons 9, 17, 20-22. Consistent with this, other researchers have observed dolomite in deep loess samples near pedons 21 and 22 (Ruhe, 1984;Pye and Johnson, 1988;Muhs et al, 2001). To ascertain definitively if dolomite was present in any of these more southern profiles, we attempted to get samples in collaboration with D. Muhs (US Geological Survey).…”
Section: Mineralogical Composition Of the Pedonsmentioning
confidence: 64%
See 2 more Smart Citations
“…The model was also consistent with a small amount of dolomite at depth in pedons 9, 17, 20-22. Consistent with this, other researchers have observed dolomite in deep loess samples near pedons 21 and 22 (Ruhe, 1984;Pye and Johnson, 1988;Muhs et al, 2001). To ascertain definitively if dolomite was present in any of these more southern profiles, we attempted to get samples in collaboration with D. Muhs (US Geological Survey).…”
Section: Mineralogical Composition Of the Pedonsmentioning
confidence: 64%
“…In our previous study , we relied on published chemical analyses and X-ray diffraction data for the Peoria loess sampled from pedons along the Mississippi transect (Muhs et al, 2001). Williams et al (2010) also reported new quantitative X-ray diffraction (XRD) analyses of Muhs' samples from pedons 1 (Clayton County, IL), 13 (Lauderdale County, TN), and 22 (St. Francisville, LA).…”
Section: Mineralogical Composition Of the Pedonsmentioning
confidence: 99%
See 1 more Smart Citation
“…The re sults obtained were ver i fied based on the Till-3 ref er ence ma te rial (Geo chem i cal Soil and Till Ref er ence Ma te ri als cer ti fied by Breitländer Com pany). Changes in the ox ides con tent within soil pro file were eval u ated on the ba sis of for mu las given by Breemen and Buurman (1998), and Muhs et al (2001).…”
Section: Methodsmentioning
confidence: 99%
“…It has been useful in characterizing pedon and landscape processes such as direction or extent of weathering and determining the nature or origins of parent materials (Jersak et al 1997;Wilcke and Amelung 1996;Muhs et al 2001).…”
Section: Geochemical Applications Within Soil Surveymentioning
confidence: 99%